Chronic osteomyelitis mimicking sarcoma. Issue 3 (1st March 2003) - Gulmann, C; Young, O; Tolan, M; O'Riordan, D; Leader, M
Abstract : This report describes a rare case of chronic osteomyelitis in a 60 year old man mimicking a soft tissue sarcoma. Chronic osteomyelitis is an infrequent cause of a soft tissue mass and is usually diagnosed clinically by a combination of radiology and microbiology. Rarely, COM can mimic a primary bony neoplasm, but this is the first reported case where it mimicked a soft tissue sarcoma. The clinical, radiological, and histological appearances of this case will be discussed.